Beyond Age and Cause: A Multidimensional Characterization of Fatal Farm Injuries in Ireland. Issue 2 (3rd April 2023) - Mohammadrezaei, Mohammad; Meredith, David; McNamara, John
ABSTRACT: The study seeks to enhance understanding of the complex nature of fatal farm injuries and thereby support the development of targeted safety messages or interventions. The research analyses fatal farm injuries surveillance data collected by the Health and Safety Authority (Ireland) for the period 2004–2018. Utilizing Non-Linear Canonical Correlation Analysis (NLCCA) to identify similarities and differences between 274 fatal injuries, multiple interactions and correlations between two sets of variables were identified. The analysis identified two major patterns of injury. The first relates to older farmers (60+) who were killed due to being struck by an object in motion, i.e. a tractor or machine. These injuries occurred mainly during the summer or winter between 13:00 and 18:00 in the Southern-Eastern regions. The second pattern also relates to older farmers, however these fatalities are associated with beef production and the primary cause of injury was being kicked or crushed by livestock. These injuries commonly occur in the Border, Midland, and Western regions where fatalities are prevalent during spring and outside of normal working hours. Assessing interactions between variables demonstrates to whom, how, when, and where fatal injuries affect different groups within the farm population. These findings provide regulators and farm safety stakeholders with key insights into background characteristics of fatal injuries including type of enterprise, time of day, season, and regional location that should be used to develop safety awareness, training, and targeted interventions to at-risk populations.